Measuring task-specific perceptions of the World Wide Web. - Page-Thomas K (Behaviour & Information Technology)
This paper describes the development of multi-item scales for measuring user perceptions of the ease-of-use and usefulness of the Web (hereafter web), incorporating a system task focus into the scales dimensional structure (e.g. how easy or useful the web is for information search, communication and or purchasing). The items are tested on 2077 web users recruited using a web survey, revealing four factors for each scale. Perceived ease-of-web use consists of learning, search and find, transaction and communication ease, and perceived web usefulness consists of communication, purchase, information search and acquisition, and access to quality products and information. A regression analysis on web usage frequency shows how easy users find it to learn how to use the web and how useful the web is for purchasing are the best predictors of how frequently they will use the web. These results highlight the importance of training users how to effectively use hypermedia-based systems like the web, and the design of systems that are easy to navigate and that provide advanced functionality for transactional activity.